Kecelakaan Kerja pada Perusahaan Konstruksi: Sebuah Telaah Literatur - Syafiq, Umar; Perdhana, Mirwan Surya (Diponegoro Journal of Management, 2018)
The purpose of this conceptual research is to present the current literature review related to Causes of Occupational Accidents in Construction Companies. Construction companies are currently the most significant contributor to the number of occupational accidents  in  Indonesia.  In  fact,  there  are  already  specific  safety K3  guidelines  for construction companies that should be the handle of construction companies to reduce the number of work accidents. Various kinds of literature related to the causes of occupational accidents at construction companies are discussed in this study, along with the upcoming research agenda related to change management.